Performance Evaluation to Provide StaaS to IoT Devices in Fog Computing Environment - Machado, José dos Santos; Silva, Danilo Souza; Fontes, Raphael Silva; Menezes, Adauto Cavalcante; Moreno, Edward David; Ribeiro, Admilson de Ribamar Lima (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2018)
This work presents the concept of Fog Computing, its theoretical contextualization, the related works, and performsthe analysis of a Fog Computing to provide StaaS (Storage as a Service) on IoT devices using embedded systems platforms,in addition for comparing its results with those obtained by a high-performance server. In this article, we use OwnCloud andBenchmark SmashBox (for data transfer analysis). The results showed that the implementation of this service in embeddedsystems devices can be a good alternative to reduce one of these problems, in this case, the storage of data, which currentlyreaches IoT devices.